The Role of Social Media Platforms as a Means of Digital Marketing Innovation for Startups in Indonesia - Widjaja, Trees Nia Sari; Putri, Melati Triani; Renatasari, Distya Ayu; Wardhana, Hendra; Redjeki, Finny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the role of social media platforms as an innovative digital marketing tool for startups in Indonesia. With the growing number of digital startups and internet penetration, social media has become a strategic platform to build brand awareness, engage customers, and enhance business growth. The research adopts a qualitative literature review approach, analyzing various studies and cases in the Indonesian startup ecosystem. Findings suggest that platforms like Instagram, TikTok, Facebook, and LinkedIn significantly contribute to marketing innovation by enabling low-cost promotions, real-time customer interaction, and viral campaigns. The paper also identifies challenges including algorithm changes, content saturation, and limited human resources. Strategic recommendations are provided for startups to optimize their social media presence.